The combined effects of questioning technique and interviewer manner on false confessions. Issue 3 (24th September 2018) - Paton, Wendy; Bain, Stella A.; Gozna, Lynsey; Gilchrist, Elizabeth; Heim, Derek; Gardner, Euan; Cairns, David; McGranaghan, Paul; Fischer, Rico
Abstract: Although it is known that interrogation tactics can elicit false confessions and interviewer manner may determine the outcome of an interview, the combined effects of questioning technique and interviewer manner on false confessions have not been examined empirically. Following a false accusation of theft, participants were interviewed in one of four questioning conditions (minimisation, repetitive questioning, leading questions, and nonleading questions) in which interviewers adopted a stern or friendly manner. Perceptions of pressure to confess and interviewer behaviours were measured. Significantly more false confessions were elicited using nonleading questions rather than repetitive questioning. More false confessions were elicited in the friendly interviewer condition than in the stern interviewer condition. Neither interviewer manner nor questioning technique had a significant effect on subjective ratings of pressure to confess. The finding that false confessions may be elicited in the absence of coercive tactics may have implications for informing best practices in investigative interviewing.